Design Development of Semi-Automated Barrel Lifting and Tilting Trolley - Baharudin, Mohamad Adam; BIN YUSOF, MOHD SALLEHUDDIN; Norazwan, Mohammad Hafiz (Research Progress in Mechanical and Manufacturing Engineering, 2024)
The aim of this study is to presents the design and development of a semi-automatic barrel lifting and tilting trolley. The purpose of this project is to enhance efficiency and reduce manual labor in industries that involve the handling and transportation of heavy barrels. The trolley incorporates a lifting mechanism using a linear actuator, while tilting is achieved through manual rotation facilitated by a chain and sprocket system for precise positioning. Safety features, such as a quick-release grip attached to the barrel cradle, prevent unwanted sliding during lifting and tilting operations. The development process includes four phases: conceptual design, preliminary design, detailed design, and engineering analysis. Among the three proposed trolley designs, one was selected based on the requirements and specifications. The initial step in developing a trolley mechanism involved utilizing existing patents and researching available machines in the market. This process served as inspiration for generating ideas for the design concept. Once the best design concept was determined, it was then implemented and modelled using SolidWorks software. Selected designs undergo a sustainable analysis using the Life Cycle Assessment (LCA) tool in SolidWorks. Additionally, structural analysis was conducted using Ansys to assess the structural integrity of the selected design. Findings from this design and analysis process provide valuable insights for efficient and safe barrel handling in industrial settings.